Sickness rate of modern youth and ways of its improvement. - Bashavets N.A (Kharkov National Pedagogical University, 2011)
The paper presents the state of health of the 1 - 4th year students of Odessa's higher schools displayed at the medical examination held from 2005 to 2009; analyzes their dynamics. The research data in 2009 were the results of medical examination of 23914 students. The paper analyzes publications of some modern scientists raising the problem of worsening of modern youth's health. It is established that from 2005 to 2009 there happened a reduction in the number of students referred to the basic medical group - from 69,6 % to 65,2 %, the preparatory one - from 16,1% to 13,8%. There is an increase in the number of students referred to a special "A" group - from 11,9 % to 18 %, a special "B" group - from 1,7% to 2 %, and the exempts - from 0,7 % to 1 %. The author delineates some basic directions for modern youth's health improvement.